Higher-order cycling skills among 11- to 13-year-old cyclists and relationships with cycling experience, risky behavior, crashes and self-assessed skill. (December 2018) - Twisk, Divera; Wesseling, Simone; Vlakveld, Willem; Vissers, Jan; Hegeman, Geertje; Hukker, Nikki; Roelofs, Erik; Slinger, Wilma
Abstract: Introduction: In the Netherlands, young cyclists are extremely vulnerable in traffic, which may partly be due to their still underdeveloped higher-order cycling skill. So far, knowledge on their actual level of skill is lacking. Using a computerized test battery mimicking real-life risky traffic conditions, this study assessed the level of higher-order cycling skill in children 11 and 12 years of age and tested the hypothesis that these skills show caveats. Furthermore, factors potentially influencing the development and impact of these skills were studied, such as cycling experience, risky road behavior, crash involvement, and self-assessed skill. Method: A total of 335 students (49% female) completed computerized tests on hazard perception, gap acceptance, blind spot strategies, and priority decisions in traffic, and completed questionnaires on cycling experience, risky cycling behavior, crashes, and self-assessment of cycling skill. Results: On the hazard perception test, one-third of the participants missed at least half of the number of hazards. They made errors in about 50% of the priority decisions, accepted critical gaps when crossing the road, and conversely rejected safe gaps; only 1% of the participants identified all blind spots of a truck correctly, while 69% made unsafe decisions when interacting with trucks in traffic scenarios. Overall, in complex traffic situations performance was worse than in simple ones. The hypothesis of lack of skills was therefore accepted. However, the study failed to demonstrate consistent relationships between subtest performance and cycling experience, risky behavior, crashes, and self-assessed skill, which weakens the theoretical assumptions concerning the subtests. Conclusions: The results suggest that children at the end of primary school are still lacking elementary skills for safe cycling, calling for measures to accelerate skill development. Practical applications: Test batteries are essential tools for systematically monitoring skill development in cyclists, evaluating education programs, and for guiding the development of effective road safety education. The next step is the validation of such batteries. Highlights: Cycling crashes increase when youngsters leave primary school. Use of laptop-based tests mimicking potentially risky real traffic situations. 11- to 13-year-olds have caveats in higher-order cycling skills. Frequent errors in priority at intersections, crossing decisions, identification of hazards, and interactions with trucks. Errors increase with increasing traffic complexity.